The effect of using the formative evaluation in teaching Arabic calligraphy on the achievement of the second stage students - Department of Art Education (Journal of the College of Basic Education, 2023)
If it is necessary to improve the productive process, then we must pay attention to the development of the student's thinking.The student who is the focus of this process, we prepare for him the interest that is appropriate to the scientific level.And educationally, education has expanded in our present time after the technical and technological development that took place on thethe world in general, and education in particular, so it is no longer limited to teaching the subject.Rather, it expands the student's wealth of knowledge and increases his concepts, knowledge, and terminology.And work on developing his mental ability to understand and assimilate.Universities and educational institutions have taken care to prepare curricula that are suitable forThe fields of knowledge in all the elements of the curriculum “objectives, material, method, evaluation” are concerned with whatPositive changes occur in the student's educational attitudes and provide him with the means of acquiringknowledge.In order to continue the process, the educational institutions paid attention to the development of the curricula.teaching methods and methods and methods of evaluation, “as the evaluation process begins with the beginning of anyeducational program or any educational or training programme, and continues during the learning process until its end.The method by which the extent of learning is judged.”213) p. (201:The evaluation process is based on the postulate that the educational process is an organized process.sequential and sequential aims to ensure the achievement of the objectives and provide the teacher with evidence of his performanceWith the aim of improving teaching procedures and developing student learning” (215 (p. 893):The evaluation process is based on a number of foundations according to which it works on the success of the process.For the purpose of evaluating the multi-faceted academic achievement, different methods are provided to achievethat.